Stiffness Model of a 3-DOF Parallel Manipulator with Two Additional Legs. (23rd October 2014) - Yu, Guang; Wu, Jun; Wang, Liping
This paper investigates the stiffness modelling of a 3-DOF parallel manipulator with two additional legs. The stiffness model in six directions of the 3-DOF parallel manipulator with two additional legs is derived by performing condensation of DOFs for the joint connection and treatment of the fixed-end connections. Moreover, this modelling method is used to derive the stiffness model of the manipulator with zero/one additional legs. Two performance indices are given to compare the stiffness of the parallel manipulators with two additional legs with those of the manipulators with zero/one additional legs. The method not only can be used to derive the stiffness model of a redundant parallel manipulator, but also to model the stiffness of non-redundant parallel manipulators.